B cell subset composition segments clinically and serologically distinct groups in chronic cutaneous lupus erythematosus. Issue 9 (3rd June 2021) - Jenks, Scott A; Wei, Chungwen; Bugrovsky, Regina; Hill, Aisha; Wang, Xiaoqian; Rossi, Francesca M; Cashman, Kevin; Woodruff, Matthew C; Aspey, Laura D; Lim, S. Sam; Bao, Gaobin; Drenkard, Cristina; et al.
Abstract : Objective: While the contribution of B-cells to SLE is well established, its role in chronic cutaneous lupus erythematosus (CCLE) remains unclear. Here, we compare B-cell and serum auto-antibody profiles between patients with systemic lupus erythematosus (SLE), CCLE, and overlap conditions. Methods: B-cells were compared by flow cytometry amongst healthy controls, CCLE without systemic lupus (CCLE+/SLE−) and SLE patients with (SLE+/CCLE+) or without CCLE (SLE+/CCLE−). Serum was analyed for autoreactive 9G4+, anti-double-stranded DNA, anti-chromatin and anti-RNA antibodies by ELISA and for anti-RNA binding proteins (RBP) by luciferase immunoprecipitation. Results: Patients with CCLE+/SLE− share B-cell abnormalities with SLE including decreased unswitched memory and increased effector B-cells albeit at a lower level than SLE patients. Similarly, both SLE and CCLE+/SLE- patients have elevated 9G4+ IgG autoantibodies despite lower levels of anti-nucleic acid and anti-RBP antibodies in CCLE+/SLE−. CCLE+/SLE− patients could be stratified into those with SLE-like B-cell profiles and a separate group with normal B-cell profiles. The former group was more serologically active and more likely to have disseminated skin lesions. Conclusion: CCLE displays perturbations in B-cell homeostasis and partial B-cell tolerance breakdown. Our study demonstrates that this entity is immunologically heterogeneous and includes a disease segment whose B-cell compartment resembles SLE and is clinically associated with enhanced serological activity and more extensive skin disease. This picture suggests that SLE-like B-cell changes in primary CCLE may help identify patients at risk for subsequent development of SLE. B-cell profiling in CCLE might also indentify candidates who would benefit from B-cell targeted therapies.